MANAJEMEN TALENTA: PETA JALAN MEMBIDIK SUMBER DAYA MANUSIA BERKUALITAS - Erkaningrum F., Indri (VOCATIO : Jurnal Ilmiah Ilmu Administrasi dan Sekretari, 2017)
The existence of talented and qualified human resources in strategic positions becomes the company’s life blood. The imbalance of the availability and needs of talented and qualified human resources triggers unethical actions in hunting human resources. This condition unconsciously leads the company into war for talent situation and not in war with talent situation. Talent management is designed to attract, develop, and maintain talented and superior quality human resources in the company’s strategic position. The company’s capability in executing the roadmap of talent management can create sustained competitive advantage. It can be built by harmonizing the human resources and the company’s strategy. Brand for talent is built to appeal to talented human resources and makes them famous as the company’s brand.